2022
DOI: 10.3390/ijms232113583
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Mediates Skin Ulceration Syndrome Outbreak by Readjusting Lipid Metabolism in Apostichopus japonicus

Abstract: The intestinal tract is the most important location for symbiotes and pathogens, and the microbiota plays a crucial role in affecting the health of the gut and other host organs. Dysbacteriosis in the intestinal system has been proven to be significant in skin ulceration syndrome (SUS) in sea cucumbers. This study investigates whether the gut microbiota and lipid metabolites are relevant to the initiation and progression of SUS in a Vibrio-splendidus-infected sea cucumber model. The tight junction genes were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…This should also include ensuring the freshness and cleanliness of feeds while increasing the feeding rate of sea cucumbers to improve the benefits of cultivation. 10 Additionally, it is crucial to enhance farming models by implementing specific measures. This involves carefully designing culture ponds and considering the appropriate stocking densities for seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…This should also include ensuring the freshness and cleanliness of feeds while increasing the feeding rate of sea cucumbers to improve the benefits of cultivation. 10 Additionally, it is crucial to enhance farming models by implementing specific measures. This involves carefully designing culture ponds and considering the appropriate stocking densities for seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The coe cient of variation of body weight during the growth of A. japonicus exceeded 70%, which seriously affected the culture yield and industrial e ciency [4]. The growth performance of A. japonicus is in uenced by multiple factors such as genetics, diet, environment and microorganisms [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [17] showed that the addition of Rhamnodon lactobacillus M2-4 to the feed signi cantly altered the gut metabolism of A. japonicus, with an increase in differential lipid metabolites and lipid metabolic pathways. Zhang et al [7] found that the abundance of Psychromonas macrocephali, Propionigenium maris, and Bacillus cereus in the gut bacterial community of A. japonicus infected with skin ulcer syndrome (SUS) increased signi cantly in the host. The longchain fatty acid me tabolites triglyceride, phosphatidylethanolamine and phosphatidylglycerol interacted with each other in response to SUS.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that environmental stressors generate disorders in the symbiotic microbial community, causing diseases in holothuroids such as Apostichopus japonicus [17,18]. In recent years, there have been reports of a link between variations in the intestinal microbiota and the development of SUS in sea cucumbers [19][20][21]. However, few studies have used histology to describe tissue damage caused by the disease [13,21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been reports of a link between variations in the intestinal microbiota and the development of SUS in sea cucumbers [19][20][21]. However, few studies have used histology to describe tissue damage caused by the disease [13,21].…”
Section: Introductionmentioning
confidence: 99%